Manipulating the Placebo Response in Experimental Pain by Altering Doctor’s Performance Style - Czerniak, Efrat; Biegon, Anat; Ziv, Amitai; Karnieli-Miller, Orit; Weiser, Mark; Alon, Uri; Citron, Atay (Frontiers in Psychology, 2016)
Background: The 'placebo response' is defined as improvement of clinical outcome in individuals receiving inactive drugs. The placebo response is thought to be generated by expectation of reward through the reward circuitry of the brain. The placebo response size is known to be influenced by verbal suggestion. Here we examined the possibility of influencing the placebo response by using stage directions and scripting to manipulate the style and content of the doctor-patient encounter. Methods: 155 healthy volunteers (18-45y, 97 men) exposed to experimental pain (cold pressor test, CPT) were assessed for pain threshold and tolerance before and after receiving a placebo ointment from a “doctor” impersonated by a trained actor alternating between two distinct scripts and stage directions created by a theatre director. A >30% increase in pain threshold relative to baseline was defined as a positive response. Results: Doctor’s performance had a significant effect on the response size in placebo responders, but not in non-responders (2-way ANOVA by performance style and responder status, (F=4.296; p=.040; η2=.035) and a significant interaction term (F=5.213; p=.024). The engaging and suggestive performance style resulted in a significant increase in pain threshold relative to the more detached and preoccupied style (p=.020). Conclusions: These results support the hypothesis that manipulation of physician’s performance style to increase faith in the medication offered may have a significant beneficial effect on the size of the response to placebo analgesia. They also demonstrate that subjects not susceptible to placebo are also not susceptible to performance style.